PENERAPAN MODEL KOOPERATIF TIPE MAKE A MATCH BERBANTUAN ALAT PERAGA PANJURANG TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS II SD - Chintya Oktaviani; Andika Kusuma Wijaya; Wahyuni Oktavia (Universitas Negeri Medan, 2025)
This study aims to determines: 1) theim provement of students' understanding of mathematical concepts through the coope rativelearning model of the make a match type using props Panjurang aids on addition and subtraction materials; 2) students' responses during learning with the cooperative learning model of the make a match type using Panjurang teaching aids on addition and subtraction. There search design used in this study is one group pre -test post-test design. The sampling technique used in this study was nonprobability sampling with the purposive sampling type . The data collection instruments used were students' mathematical concept understanding question sheets and student response questionnaire sheets. There sults of the study showed that 1) there was anincrea sein understanding of mathematical concepts through the use of the make a match type cooperative model accompanied by the use of props Panjurang aids in grade II students at SDN Negeri 8 Singkawang, namely with an N-Gain valueof 0.90. 2) student responses through the make a match type cooperative learning model using props Panjurang aids on addition material were classified as very good, this was indicate d by the overall results of thepercentage of student respondent questionnaires of 93.